Tendon involvement in patients with gout: an ultrasound study of prevalence. Issue 8 (August 2016) - Ventura-Ríos, Lucio; Sánchez-Bringas, Guadalupe; Pineda, Carlos; Hernández-Díaz, Cristina; Reginato, Anthony; Alva, Magaly; Audisio, Marcelo; Bertoli, Ana; Cazenave, Tomas; Gutiérrez, Marwin; Mora, Claudia; Py, Guillermo; et al.
Abstract The objective of the present study is to evaluate, by ultrasonography (US), the prevalence in the quadriceps, patellar, and Achilles tendon involvement of gout compared to that of patients with osteoarthritis and asymptomatic marathon runners. This is a multicenter, multinational, transverse cross-sectional, and comparative study comprising 80 patients with the diagnosis of gout according to the American College of Rheumatology (ACR) criteria, compared with two control groups: 35 patients with generalized osteoarthritis according to the ACR criteria and 35 subjects who were healthy marathon runners. Demographics and clinical characteristics, such as age, gender, comorbidity, disease duration, pain at the enthesis in the knee and ankle, frequency of disease exacerbations, uric acid level more than 7.2 mg at the time of evaluation, and type of treatment, were recorded. All participants were examined by ultrasound at the quadriceps, the patellar at its proximal and distal insertion, and the Achilles tendon to detect intra-tendinous tophus or aggregates according to the OMERACT definitions. Descriptive statistics and differences between groups were analyzed by chi-square test. Sensitivity and specificity by US were calculated. The prevalence of intra-tendinous aggregates and tophi in gout was significant compared with the other groups. Both lesions were the most frequent at the distal patellar insertion, followed by the quadriceps, Achilles, and proximal patellar insertion ones. In patients with osteoarthritis (OA), intra-tendinous hyperechoic aggregates were observed in 20 % of quadriceps tendons and in 11 % of patellar tendons at its proximal insertion, while in the healthy marathon runner group, the Achilles tendon had this kind of lesion in 17 % of the subjects. Neither the OA nor the healthy marathon runners had intra-tendinous tophi. The sensitivity and specificity of US to detect tophi or aggregates were 69.6 and 92 %, respectively, tendon involvement at the lower limbs in gout is very frequent, particularly in the patellar tendon, and US possesses good sensitivity and specificity for detecting intra-tendinous tophi.